Implementasi Desain Pembelajaran Kreatif untuk Siswa Kelas Rendah di SDN Pondok Jagung Timur Kota Tangerang Selatan - Wulandari, Cahya; Riyadi, Nabilla Aisyah; Sahrurosi, Putri Adinda (TSAQOFAH, 2023)
The problem in this study is that Indonesian students in the second grade at SDN Pondok Jagung Timur have poor reading skills and poor learning outcomes. This is because teachers haven't used fun learning models, students are passive learners when teacher-centered learning is used, and students don't understand what they are learning because they don't have enough reading skills or don't want to learn to read. The Papan cerita Media, Scramble, and Picture and Picture learning models are utilized in the effort. The purpose of this study was to determine the quality of teacher and student activities in order to improve student learning outcomes in beginning reading skills. By describing school data in sentences, this study employs a qualitative research methodology. According to the study, using the Picture, Scramble, and Papan cerita Media learning models can help students in class II increase both their activity and their learning outcomes.